Exploration of Ethnomathematics in the ANRI (Arsip Nasional Republik Indonesia) Building, West Jakarta - Adrian, Muhammad; Buhairi, Fathan; Fadhilah, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This research explores the relationship between mathematics and culture in Indonesia, focusing on the ANRI building as a cultural heritage site. The research aims to develop citizenship through understanding the informal mathematical knowledge of local people and their environment. Architectural features of the building and historical artifacts, such as the musical instrument Gong Waning, reflect geometric concepts. Ethnomathematics provides a valuable framework for understanding mathematical concepts in cultural artifacts